CexE Is a Coat Protein and Virulence Factor of Diarrheagenic Pathogens - Rivas, Zachary P.; Talbot, Kacey M.; Merselis, Leidy C.; McCormack, Ryan M.; Adkins, Becky; Munson, George P. (Frontiers in Microbiology, 2020)
CexE is a 12 kDa protein that was originally reported to be present in just three strains of enterotoxigenic Escherichia coli (ETEC); a frequent cause of diarrheal illnesses worldwide. However, an examination of sequenced genomes has revealed that CexE is actually present in a majority of ETEC strains. In addition, homologs of CexE are present in enteroaggregative E. coli (EAEC), Yersinia enterocolitica, Providencia alcalifaciens, and Citrobacter rodentium. Although it has been hypothesized that CexE and its homologs are virulence factors, this has yet to be tested. Thus the primary aim of this study was to determine if these proteins contribute to pathogenicity. Our secondary aim was determine if they are secreted coat proteins. Here we report that all neonatal mice infected with a wild-type strain of C. rodentium perished. In contrast a cexE mutant was significantly attenuated with 45% neonate survival. In adult mice the wild-type strain reached significantly higher loads in the large intestines and were shed in greater numbers than cexE mutants. Secretion of the CexE homolog in EAEC is dependent upon an atypical Type I secretion system that accepts its client from the periplasm rather than the cytoplasm. Insertion mutants of cexC, the putative ATPase of the CexE secretion system, were attenuated in our murine model. In vitro we found that CexC is required for the secretion of CexE to the outer membranes of both ETEC and C. rodentium. Secretion is not constitutive because CexE accumulates in the periplasm when the two pathogens are cultured under non-inducing conditions. Although secretion conditions differ between ETEC and C. rodentium, secreted CexE remains predominantly associated with the outer membranes of both species. In aggregate these findings demonstrate that CexE is a secreted coat protein and virulence factor that promotes colonization of host intestinal tissues by enteric pathogens.